Pembuatan model alat pembuang panas untuk air pendingin alat praktikum heat exchanger merk PA Hilton seri H101 di laboratorium teknik mesin - Hadimi Hadimi; Rusadi Rusadi (TURBO [Tulisan Riset Berbasis Online], 2022)
Heat Exhanger Service Unit H101/08490 P.A Hilton Ltd that use for heat transfer experiment has a weakness because the water flow from the unit after taking heat will directly enter the storage tank, still have a high temperatureÂ  ( >33oC ). The use of practicum equipment for a experiment with a long enough duration will cause the cooling water are used have a high temperature and be ineffective for the heat exchanger cooling process. The purpose of making a Cooling Tower Type Heat Dissipator Model for Heat Exhanger Service Unit H101/08490Â  P.A Hilton Ltd so that the cooling water used to carry out the practicum will be maintained at a temperature of 28oC-33oC. Maintaining the stability of the cooling water temperature is expected to produce data that does not vary too much and can be done in a fairly long data collection range. The results of the performance and effectiveness test of cooling tower cooling show that the temperature increase is only 4oC for 3 hours of testing and the cooling effectiveness increases and is relatively constant during the test time. This shows that the cooling system with a cooling tower can be used as a supporting medium for heat exchanger practicum in the Mechanical Engineering department.